52.9k views
4 votes
-2p- 4=2 I need help please

User Joe Sloan
by
5.0k points

2 Answers

0 votes

Answer: p = -3

Explanation:

Add '4' to each side of the equation.

-4 + 4 + -2p = 2 + 4

Combine like terms: -4 + 4 = 0

0 + -2p = 2 + 4

-2p = 2 + 4

Combine like terms: 2 + 4 = 6

-2p = 6

Divide each side by '-2'.

p = -3

Simplifying

p = -3

User JeremiahDotNet
by
4.9k points
4 votes

Answer:

p=-3

Explanation:

You have to isolate p, so you first get rid of the constant (-4). You do so by adding four, resulting in -2p=6. Then you divide by -2 to get p=-3.

User Ntysdd
by
4.7k points